2016
DOI: 10.1007/s00217-015-2626-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evolution of volatile compounds during ripening of ‘Nebbiolo,’ ‘Dolcetto’ and ‘Barbera’ (Vitis vinifera L.) neutral grapes by SBSE–GC/MS

Abstract: The evolution of pre-fermentative volatiles and of the global aroma potential in three Italian neutral varieties ('Nebbiolo', 'Barbera' and 'Dolcetto') was assessed from véraison to harvest by SBSE-GC/MS. C6 and C9 compounds, benzene derivatives, bound monoterpenes and sesquiterpenes showed differences among varieties in quantity and profiles during berry ripening. Quantitatively, the most of total monoterpenes, C-13 norisoprenoids and sesquiterpenes were detected after acid hydrolysis. Among prefermentative n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
1
10
0
2
Order By: Relevance
“…β-Damascenone was found by SBSE-GC-MS throughout the screening of three different natural grapes (Vitis vinifera L.) of Nebbiolo, Dolcetto, and Barbara. These grapes that contained the lowest amount of β-damascenone (48.2±26.1 to 265.2±83.0 μg/kg) also had a lower level of norisoprenoids than Cowart observed in this study (24). Ristic et al (25) who investigated the C13 norisoprenoid by a solid-phase microextraction GC-MS found that Vitis vinifera L. cv.…”
supporting
confidence: 43%
“…β-Damascenone was found by SBSE-GC-MS throughout the screening of three different natural grapes (Vitis vinifera L.) of Nebbiolo, Dolcetto, and Barbara. These grapes that contained the lowest amount of β-damascenone (48.2±26.1 to 265.2±83.0 μg/kg) also had a lower level of norisoprenoids than Cowart observed in this study (24). Ristic et al (25) who investigated the C13 norisoprenoid by a solid-phase microextraction GC-MS found that Vitis vinifera L. cv.…”
supporting
confidence: 43%
“…formed soon and stable, maxima 17 ppb [15]; idem, with maxima 7 ppb [66] β-Ionone Not found; yes in frozen grapes [136]; not in wines [137]; <0.11 ppb in frozen grapes [12] Generally yes; not found in [12] Maxima (1.9 ppb) after short aging, stable with time [14]; formed soon, stable for a while, maxima 7.7 ppb [15] TDN Not found; yes in frozen grapes [136]; not in wines [137]; 1-6 ppb (5-30% of levels found in harsh acid hydrolysis) in frozen grapes [12] 8 ppb [138]; detected by GCO [12] 3 ppb [138]; 2-23 ppb depending varieties [12] Continuously formed, maxima 9 ppb [66] Terpenes Linalool Generally present; not found in Portuguese reds [140]; not found in Melon B [141]; not found in Shiraz [144]; found at low levels (less than 7% geraniol 1% total terpenes) [144] 3% levels found in enzymatic [138]; 10-50% of levels found in enzymatic [12] Found only in mild acid hydrolysis [141]; maxima after fermentation, sharp decrease in aging [14]; in Grenache, maxima after short aging [143];…”
Section: Grape Aroma Vs Grape-derived Wine Aromamentioning
confidence: 97%
“…The first section deals with glycosidic precursors, the second with other precursors, and the two last sections with glutathionyl and cysteinyl precursors and DMS precursors. [23,57] and frozen grapes [136]; not in wines [137]; 0.17-0.5 ppb in frozen grapes [12] 26 ppb [138]; detected by GCO [139]; 4-28 ppb depending varieties, unclear pulp/skin distribution [140]; 4-20 ppb depending location [140]; levels correlated to total norisoprenoids by enzymatic [141]; 2-4.5 ppb depending varieties [12] Detected by GCO [142]; maxima (3.3 ppb) after short aging, then steady decrease [14]; steady increase all the aging in fermented samples [143]; maxima 7.1-7.3 ppb after medium aging in unfermented controls [143];…”
Section: Grape Aroma Vs Grape-derived Wine Aromamentioning
confidence: 99%
“…Muitos norisoprenoides também estão associados a aromas de frutas ou de flores. Em geral, o acúmulo de compostos voláteis como os monoterpenos, sesquiterpenos e C-13 norisoprenoides ocorre após o pintor (Carlomagno et al, 2016). Estes autores também destacaram que os compostos voláteis sob a forma livre são derivados de metabolitos lipídicos e que apresentam uma importante contribuição para a composição aromática varietal.…”
Section: Different Classes Of Aromatic Compounds Present In Grapes Anunclassified
“…Nas sementes maduras, o tegumento possui a função de proteção mecânica para o embrião e ajuda na manutenção da dormência da semente (Ristic e Iland, 2005). As mudanças nos taninos e demais compostos fenólicos das sementes durante a maturação são intensamente percebidas nos atributos sensoriais das uvas e nas características gustativas dos vinhos (Fredes et al, 2010 Kuhn et al (2013) (mono e sesquiterpenos, norisoprenoides e metoxipirazinas), Robinson et al (2014) (mono e sesquiterpenos e metoxipirazinas), Gonzáles-Barreiro et al (2015) (mono e sesquiterpenos e norisoprenoides).e Carlomagno et al (2016) (mono e sesquiterpenos e norisoprenoides). Fregoni (1999) (fresh mass, diameter and volume), Ribéreau-Gayon et al (2006) (mono and sesquiterpenes, norisoprenoids and methoxypyrazines), Keller (2010) (methoxypyrazines), Zhu et al (2012) (methoxypyrazines), Kuhn et al (2013) (mono and sesquiterpenes, norisoprenoids and methoxypyrazines), Robinson et al (2014) (mono and sesquiterpenes and methoxypyrazines), Gonzáles-Barreiro et al (2015) (mono and sesquiterpenes and norisoprenoids) e Carlomagno et al (2016) (mono and sesquiterpenes and norisoprenoids).…”
Section: Maturação Das Sementesunclassified